Facial expressivity in the course of schizophrenia and depression - Gaebel, Wolfgang; W lwer, Wolfgang (European archives of psychiatry and clinical neuroscience, 2004)
This study investigates the nosological specificity and time stability of reduced facial expressivity in schizophrenia by means of objective measurement. Facial expression in an emotional interview was evaluated using the "Facial Action Coding System" in 33 acute schizophrenia patients and 23 acute depressive patients in comparison with 21 nonpatient controls, each assessed twice within 4 weeks, and in 36 partly remitted schizophrenia patients assessed twice within 3 months. Acute schizophrenia patients showed reduced facial activity especially in the upper face and in facial activity often used as communicative signs or as signs of positive emotions. As depressive patients showed a comparable pattern of facial activity, nosological specificity is questionable. This pattern remained stable in the acute illness course and was almost identical in remitted schizophrenia patients, indicating a marked time stability of attenuated facial expressivity in schizophrenia and--for the acute phase assessed--in depression.